Endoscopic papillectomy of benign ampular lesion: Report of a case and review of the literature - Torreblanca-Nava, Juan Alberto (2020)
Introduction: The lesions of the ampulla of Vater represents around 0,5 % of gastrointestinal neoplasms. Case report: Symptoms are not specific, so its diagnostic is incidental. The biopsy of the ampulla of Vater has a false - negative of 60 % for adenocarcinoma, for that reason all adenomas ones the diagnosticated must be resected, because of the high risk of malignancy; having a survival of 67 % at five years. Conclusion: We report the case of a patient with an adenoma in the ampulla of Vater who underwent endoscopic papilectomy.